Evaluation of the Implementation of Teacher Professional Development Policy in the Digital Era fromAspects of Public Administration - Jesika Puteri; Novilasari Novilasari; Tiara Lestari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This community service activity aims to evaluate the implementation of teacher professional development policies in the digital era from a public administration perspective. The activity was conducted through socialization and mentoring sessions for teachers at SDN 2 Bukit Batu on March 7, 2024. A descriptive and participatory approach was employed, using interactive presentations, case studies, and the distribution of informational materials. The results indicate that some teachers still experience difficulties in understanding teacher professional development policies, particularly in relation to the use of digital technology in administration and learning processes. However, the socialization activities improved teachers' understanding of policy objectives, professional development strategies, and the importance of digital adaptation in supporting professional performance. The activity also fostered educational collaboration and generated innovative ideas for improving administration. Overall, this community service program contributes to strengthening human resource capacity at the school level and supports the effective implementation of public policies in the education sector.